The influence of socioeconomic status on patient survival on chronic dialysis. Issue 4 (9th April 2015) - Ward, Frank L.; O'Kelly, Patrick; Donohue, Fionnuala; O'Haiseadha, Coilín; Haase, Trutz; Pratschke, Jonathan; deFreitas, Declan G.; Johnson, Howard; O'Seaghdha, Conall M.; Conlon, Peter J.
Abstract Socioeconomic status (SES) has been linked to worse end‐stage kidney disease survival. The effect of SES on survival on chronic dialysis, including the impact of transplantation, was examined. A retrospective, observational study investigated the association of SES with dialysis patient survival, with censoring at time of transplantation. Adult patients commencing dialysis from 1990 to 2009 in an Irish tertiary center received a spatial SES score using the 2011 Pobal Haase‐Pratschke Deprivation Index and were compared by quartile. Cox proportional hazard models and Kaplan–Meier survival analysis examined any association of SES with survival. The 1794 patients included had a median follow‐up of 3.8 years. Patients in the lowest SES area quartile were significantly younger than the highest, mean age 56.7 vs. 59 years, P = 0.006, respectively. There was no association between SES area score and survival in an unadjusted model (hazard ratio [HR] 1.00, 95% confidence interval [CI] 0.99–1.01). Survival in the highest SES area quartile was superior to the lowest SES in a multivariable adjusted model including age, gender, and dialysis modality (HR 0.83, 95% CI 0.70–0.99, P = 0.04). These results were only mildly attenuated by censoring at time of transplantation (highest SES area quartile deprived vs. lowest SES area quartile, HR 0.85, 95% CI 0.70–1.03, P = 0.09). Superior patient survival was identified in the highest SES areas compared with the lowest following age‐adjusted analyses, despite the older population in the most affluent areas. Further research should focus on identifying modifiable targets for intervention that account for this socioeconomic‐related survival advantage.